Implementation of Independence Principles in Running Notary Profession - Ghaida Nabilah (Authentica, 2022)
Notaries in carrying out their positions as General Officials, apart from being bound by a Position Regulation, Code of Ethics, and also bound by the oath of office pronounced when appointed as a Notary, where the Notary is to carry out his position in a trustworthy, honest, thorough, independent, and impartial manner. as stipulated in Article 4 paragraph (2) Notary Office Act. The formulations in this study are: (1) How is the application of the principle of independence in carrying out the position of a notary public? (2) How is the legal consequence of a principle of independence by a notary public? The research conducted is normative legal research with an invited approach and a conceptual approach. Legal material engineering is carried out through the literature study. The legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. Meanwhile, the source of legal material is literature study (library research). The data technique used in this research is the literature study data method. Based on the results of the research, the form of the Notary is written in carrying out his duties and positions, the work of the Notary is working properly and professionally in accordance with the orders of the Law and the results of the second research. a result of the legal environment, the Notary is not independent in carrying out his obligations, it has an impact on the deed he makes.Keywords: Principle of Independence, Sanctions, Notary